2015
DOI: 10.3748/wjg.v21.i38.10890
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding in Scotland 2000-2010: Improved outcomes but a significant weekend effect

Abstract: Despite reduction in mortality for UGIB in Scotland during 2000-2010, weekend admissions show a consistently higher mortality and greater lengths of stay compared with weekdays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 32 publications
10
57
2
1
Order By: Relevance
“…Mortality was in-hospital in all studies in North America, whereas 30-day mortality was reported in some studies in Asia 8,12 and Europe. 2,3,7,[19][20][21][22] Thirty-day mortality includes all-cause deaths occurring only within 30 days of hospitalization and after being discharged from the hospital. For in-hospital mortality, all mortality will be counted, so long as the patient stays in the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mortality was in-hospital in all studies in North America, whereas 30-day mortality was reported in some studies in Asia 8,12 and Europe. 2,3,7,[19][20][21][22] Thirty-day mortality includes all-cause deaths occurring only within 30 days of hospitalization and after being discharged from the hospital. For in-hospital mortality, all mortality will be counted, so long as the patient stays in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,7,[18][19][20][21][22] Six studies reported patients with UGIH caused by peptic ulcer, 8,10,12,19,20,22 one study included patients with bleeding gastroduodenal angiodysplasia, 17 three demonstrated the sources of bleeding were from the esophagus varix, 11,13,15 and 10 studies included patients with both variceal and nonvariceal UGIH. 2,3,[5][6][7]14,16,18,21,22 Most recruited studies defined the ''off-hours'' as weekends only, [4][5][6][7]11,[13][14][15][16][17]21 while four studies defined it as weekends and public holidays; 3,8,12,18 one study defined it as weekends and nighttime, 20 and one study defined it as nighttime only. 19 Three studies reported results by comparison to weekend admissions as well as nighttime admissions.…”
Section: Description Of the Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations